A Rare Case of Benign Oncocytic Cystadenoma of Parotid Gland - R Prathipa; Vimal Chander; S Prakashiny (Journal of Clinical and Diagnostic Research)
Benign oncocytic cystadenoma of the parotid gland is a rare salivary gland tumour, constituting less than 1% of all salivary gland neoplasms. It is characterised by cystic spaces lined with bilayered oncocytic epithelium, composed of eosinophilic granular cytoplasm due to abundant mitochondria. While these tumours are typically asymptomatic, they can present as painless, slow-growing swellings in the preauricular region, often leading to misdiagnosis as other benign salivary gland tumours. Authors hereby, present the case of a 71-year-old female with recurrent right-sided parotid swelling. Eight years prior, she was diagnosed with low-grade mucoepidermoid carcinoma of the right submandibular gland. One year ago, she underwent total parotidectomy for a recurrent swelling, which was diagnosed histopathologically as a mucus retention cyst. Three months ago, she developed another swelling in the same region, prompting excision and biopsy. Histopathology revealed a cystic lesion lined by bilayered oncocytic epithelium with papillary projections, focal lymphoid aggregates and no evidence of malignancy, confirming oncocytic cystadenoma. Oncocytic cystadenomas present diagnostic challenges due to their rarity and overlap with other salivary gland lesions. Surgical excision is curative, with a low recurrence rate. Awareness of this rare entity is essential for accurate diagnosis and management.